Self-Efficacy in Disaster Preparedness: Insights from Nurses in Emergency and Intensive Care Units - Vranada, Aric; Anggriawan, Ferri; Wang, Tsae-Jyy (Media Keperawatan Indonesia, 2024)
Self-efficacy is a critical factor influencing nurses' performance in disaster scenarios, particularly in high-pressure environments like Emergency Departments (ED) and Intensive Care Units (ICU). This study aimed to evaluate the self-efficacy of nurses in disaster preparedness and identify its key predictors, including demographic characteristics, training experience, and professional factors. A cross-sectional survey was conducted among 185 nurses working in the ED and ICU of three hospitals in Yogyakarta, Indonesia. Data were collected from January to February 2024 using a structured questionnaire that included the Disaster Response Self-Efficacy Scale (DRSES). Descriptive statistics summarized demographic data and self-efficacy scores. Inferential analyses, including t-tests, ANOVA, and multiple regression, were performed to explore relationships between self-efficacy and potential predictors, with statistical significance set at p < 0.05. Disaster training experience emerged as the strongest predictor of self-efficacy (β = 0.65, p < 0.001), with nurses who underwent regular training demonstrating significantly higher confidence. Years of experience (β = 0.48, p = 0.01) and age (β = 0.25, p = 0.04) were also positively associated with self-efficacy. However, gender, education level, and marital status showed weak and non-significant correlations (r = 0.12–0.18, p > 0.05). Correlation analysis reinforced the importance of disaster training (r = 0.65, p < 0.001) and professional experience (r = 0.48, p = 0.01) in shaping self-efficacy. The findings underscore the importance of regular disaster training and leveraging professional experience to enhance self-efficacy among ED and ICU nurses. Policymakers and hospital administrators should prioritize targeted training programs to build a resilient nursing workforce capable of responding effectively to disasters